Covering All the Bases in Genetics: Simple Shorthands and Diagrams for Teaching Base Pairing to Biology Undergraduates - Sergei Kuchin (American Society for Microbiology, 2011)
Explaining base pairing is an important element in teaching undergraduate genetics. I propose a teaching approach that aims to close the gap between the mantra “A pairs with T, and G pairs with C” and the “intimidating” chemical diagrams. The approach offers a set of simple “shorthands” for the key bases that can be used to quickly deduce all canonical and wobble pairs that the students need to know. The approach can be further developed to analyze mutagenic mismatch pairing.